Right Cervical Vagotomy Aggravates Viral Myocarditis in Mice Via the Cholinergic Anti-inflammatory Pathway - Li-Sha, Ge; Xing-Xing, Chen; Lian-Pin, Wu; De-Pu, Zhou; Xiao-Wei, Li; Jia-Feng, Lin; Yue-Chun, Li (Frontiers in Pharmacology, 2017)
The autonomic nervous system dysfunction with increased sympathetic activity and withdrawal of vagal activity may play an important role in the pathogenesis of viral myocarditis. The vagus nerve can modulate the immune response and control inflammation through a ‘cholinergic anti-inflammatory pathway’ dependent on the α7-nicotinic acetylcholine receptor (α7nAChR). Although the role of β-adrenergic stimulation on viral myocarditis has been investigated in our pervious studies, the direct effect of vagal tone in this setting has not been yet studied. Therefore, in the present study, we investigated the effects of cervical vagotomy in a murine model of viral myocarditis. In a coxsackievirus B3 murine myocarditis model (Balb/c), effects of right cervical vagotomy and nAChR agonist nicotine on echocardiography, myocardial histopathology, viral RNA, and proinflammatory cytokine levels were studied. We found that right cervical vagotomy inhibited the cholinergic anti-inflammatory pathway, aggravated myocardial lesions, up-regulated the expression of TNF-α, IL-1β, and IL-6, and worsened the impaired left ventricular function in murine viral myocarditis, and these changes were reversed by co-treatment with nicotine by activating the cholinergic anti-inflammatory pathway. These results indicate that vagal nerve plays an important role in mediating the anti-inflammatory effect in viral myocarditis, and that cholinergic stimulation with nicotine also plays its peripheral anti-inflammatory role relying on α7nAChR, without requirement for the integrity of vagal nerve in the model. The findings suggest that vagus nerve stimulation mediated inhibition of the inflammatory processes likely provide important benefits in myocarditis treatment.